Projected losses of global mammal and bird ecological strategies - Robert S. C. Cooke (Nature Portfolio, 2019)
Animal diversity, measured in numbers of species, is rapidly being lost to extinction. Here, Cooke et al. show that the diversity of ecological strategies employed by land mammals and birds is also expected to narrow towards small, fecund, insect-eating generalists with fast-paced life histories.